2013
DOI: 10.1111/eci.12152
|View full text |Cite
|
Sign up to set email alerts
|

Symptom patterns can distinguish diverticular disease from irritable bowel syndrome

Abstract: Abdominal pain lasting for more than 24 h discriminates patients with DD compared with those with IBS. Identifying this symptom could be an appropriate strategy to define the diagnosis and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 31 publications
1
64
0
2
Order By: Relevance
“…This is because IBS and SUDD are not the same clinical entity, as showed by clinical data currently available. IBS and SUDD do not share the same epidemiology [7,9] but only part of clinical features, and patients with SUDD do not generally fulfill IBS criteria [10,11]. Moreover, the characteristics of the abdominal pain (left lower-abdominal pain lasting for more than 24 h characterizes SUDD, diffuse and short-lived abdominal pain characterizes IBS) is likely the most effective clinical tool in discriminating between patients with SUDD and those having IBS [10,11].…”
Section: Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because IBS and SUDD are not the same clinical entity, as showed by clinical data currently available. IBS and SUDD do not share the same epidemiology [7,9] but only part of clinical features, and patients with SUDD do not generally fulfill IBS criteria [10,11]. Moreover, the characteristics of the abdominal pain (left lower-abdominal pain lasting for more than 24 h characterizes SUDD, diffuse and short-lived abdominal pain characterizes IBS) is likely the most effective clinical tool in discriminating between patients with SUDD and those having IBS [10,11].…”
Section: Inflammationmentioning
confidence: 99%
“…IBS and SUDD do not share the same epidemiology [7,9] but only part of clinical features, and patients with SUDD do not generally fulfill IBS criteria [10,11]. Moreover, the characteristics of the abdominal pain (left lower-abdominal pain lasting for more than 24 h characterizes SUDD, diffuse and short-lived abdominal pain characterizes IBS) is likely the most effective clinical tool in discriminating between patients with SUDD and those having IBS [10,11]. Finally, persistence of symptoms following an episode of acute diverticulitis has been linked to several factors, ranging from significant attenuation in serotonin-transporter expression to persistence of low-grade inflammation [12][13][14].…”
Section: Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms consistent with IBS are common among patients with DD, and this symptomology has been reported as significantly higher in the DD patients when compared to non-DD controls[103-105]. However, this overlap of symptoms can cause diverticulitis to be misdiagnosed as IBS[104].…”
Section: Alternative Diet For Diverticulitismentioning
confidence: 99%
“…Patient with DD will sustain severe symptoms than IBS without diverticulum. Cuomo et al[105] suggested that these symptoms may be used to differentiate the patients with DD from those with IBS. However, their study design was based upon a patient population presenting with fever and requiring hospitalization and treatment, so that cases of diverticulum without inflammation were not considered.…”
Section: Alternative Diet For Diverticulitismentioning
confidence: 99%